Quantitative Characterization of the Chemical Space Governed by Human Carbonic Anhydrases and selenium-containing derivatives of solfonamides - Behnam Rasti (Universidade de São Paulo, 2022)
Abstract Due to the fact that different isoforms of carbonic anhydrase play distinct physiological roles, their diseases/disorders involvement are different as well. Involvement in major disorders such as glaucoma, epilepsy, Alzheimer's disease, obesity and cancers, have turned carbonic anhydrase into a popular case study in the field of rational drug design. Since carbonic anhydrases are highly similar with regard to their structures, selective inhibition of different isoforms has been a significant challenge. By applying a proteochemometrics approach, herein the chemical interaction space governed by acyl selenoureido benzensulfonamides and human carbonic anhydrases is explored. To assess the validity, robustness and predictivity power of the proteochemometrics model, a diverse set of validation methods was used. The final model is shown to provide valuable structural information that can be considered for new selective inhibitors design. Using the supplied information and to show the applicability of the constructed model, new compounds were designed. Monitoring of selectivity ratios of new designs shows very promising results with regard to their selectivity for a specific isoform of carbonic anhydrase.